Clinical Research In India: Scope, Opportunities And Challenges - V, Desai Nilesh; N, Patkar Atul; A, Shinde Shilpa; S, Kalekar Kamalakar (Asian Journal of Pharmaceutical Research and Development, 2013)
Indian pharmaceutical industry is one of the fastest growing sectors of the Indian economy and has made rapid strides over the years. From being import dependent in the 1950s, the industry has achieved self-sufficiency and gained global recognition as a producer of low cost, high quality bulk drugs and formulations. Having proved itself in the international market, India is ready to face the challenges of proving its efficiency as the preferred destination for global clinical trials. A number of factors favour India as a clinical research hub. Firstly, there are numerous government funded medical and pharmaceutical institutions with state of the art facilities, which can serve as ideal centers for multi-centered clinical trials. Secondly, India boasts of well-trained and qualified manpower, well versed in English. More importantly, there is vast clinical material, which can be utilised.